Glycosylated Hazelnut Protein as Egg White Alternatives in Nougat Foams: Rheology, Texture, and Microstructure - Atalar, Ilyas; Kurt, Abdullah; Demirci, Sultan; Elmaci, Ceren; Marasli, Serdar; Konar, Nevzat (WILEY, 2026)
This study examined Maillard-type glycosylated hazelnut protein conjugates as plant-based alternatives to egg white powder for producing aerated nougat foams. Hazelnut protein isolate (HPI) was conjugated with gum arabic (HPI-GA) or sodium alginate (HPI-SA) under optimized wet-heating conditions and used to replace egg white powder at 25, 50, 75, and 100% of the control level. Foam performance was assessed by macroscopic appearance and apparent density, steady-shear flow behavior (power-law modeling), frequency-dependent viscoelasticity (G '/G ''), texture (spreadability and back extrusion), optical microstructure, and ATR-FTIR. Replacing egg white with native HPI weakened foam structure, yielding higher density, lower viscosity/consistency, and reduced mechanical resistance. In contrast, both conjugates improved foam structuring and deformation resistance, with HPI-SA providing the most pronounced reinforcement, particularly at 25%-50% replacement, where foam properties approached those of the egg white control while maintaining stable bubble dispersion. FTIR features supported the contribution of polysaccharide moieties and stronger hydration-related interactions in conjugate systems. The findings indicate that glycosylated hazelnut proteins, especially HPI-SA, are promising functional substitutes for egg white in nougat foam formation.
Keywords: egg white replacer; glycosylation; hazelnut protein; nougat foam; rheology; Food Science & Technology